2020
DOI: 10.1111/jdv.16893
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab efficacy in reducing the severity and the psychosocial impact of moderate‐to‐severe psoriasis as assessed by the Simplified Psoriasis Index: results from the IPSI‐PSO study

Abstract: Background The utility of the Simplified Psoriasis Index (SPI), a recently developed multidomain tool for assessing psoriasis, was investigated in a study assessing response to secukinumab. Methods In an open‐label, multicentre study involving 17 French centres, patients with moderate‐to‐severe plaque psoriasis received secukinumab 300 mg subcutaneously once weekly from baseline to W4, then every 4 weeks until W48. Dermatologist‐scored SPI psoriasis severity (proSPI‐s) was compared with Psoriasis Area and Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Our Pearson's r = 0.866 actively demonstrates a strong positive linear correlation between the PASI and PO-PASI scores when assessing chronic plaque psoriasis (Table 2). Our findings are in keeping with the literature [4][5][6] . However, this provides little clinical information on how much X equals Y or the equivalence of PASI and PO-PASI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our Pearson's r = 0.866 actively demonstrates a strong positive linear correlation between the PASI and PO-PASI scores when assessing chronic plaque psoriasis (Table 2). Our findings are in keeping with the literature [4][5][6] . However, this provides little clinical information on how much X equals Y or the equivalence of PASI and PO-PASI.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that PO-PASI has a good-to-excellent interrater reliability/ agreement with the 95% confidence interval ranging from 0.803 to 0.907 (Table 2). The strong agreement implies that patients and physicians have a similar perception of psoriasis severity, in keeping with published data around patient-oriented tools 6 . Furthermore, it appears that there is a stronger correlation between the PO-PASI and the PASI Link to PO-PASI tool : https://dermnetnz.org/cme/psoriasis-po- at scores lower than 15, which is the cut-off for biological treatment in Australia.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Table 1 lists details of the clinical trials selected for this analysis . Eligible patients 18 years or older with moderate-to-severe plaque psoriasis or active psoriatic arthritis or ankylosing spondylitis were enrolled in the trials according to prespecified inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Novel biological drugs, which target TNF- α , the p40 subunit of IL-12 and IL-23, or IL-17 receptors, are effective in treating psoriasis and reducing the PASI score [ 78 ] ( Table 1 ). Interestingly, inhibition of IL-1, IL-6, or IFN- γ failed to achieve a significant clinical effect in psoriasis [ 79 ]. TNF- α inhibitors include etanercept, infliximab, adalimumab, certolizumab pegol, and golimumab [ 80 ].…”
Section: Introductionmentioning
confidence: 99%